Students' Critical Thinking Skills And Arabic Learning Outcomes Using Quizlet Media - Anwar, Muhammad Rosihan; Hilmi, Danial (Ijaz Arabi Journal of Arabic Learning, 2025)
21st-century skills are crucial for effectively transforming Arabic language learning in the digital age. This study aims to describe the changes in students' critical thinking abilities and Arabic language learning outcomes using Quizlet media. The research subjects were all Madrasah Diniyah Nurul Huda Dinoyo Malang- Indonesia students, focusing on the mubtada and khabar lesson material. The research method was a quantitative descriptive approach with a one-group pretest-posttest design. Data collection involved administering pretest and posttest questions with critical thinking indicators, including analysis, synthesis, and evaluation. The indicators for Arabic language learning outcomes were basic vocabulary skills, grammar, and the ability to analyze grammatical errors. The results indicated that the average score for students' critical thinking ability in the pretest was 18.3 (low critical thinking). In contrast, in the posttest, it was 30.00 (moderate critical thinking). As for the Arabic language learning outcomes, the pretest score was 44.67 (below the minimum completion score), and the posttest score was 81.33 (above the minimum completion score). Quizlet media can enhance students' critical thinking skills and Arabic language learning outcomes.